Clinical and Surgical Outcome After Oncovascular Surgery of Soft Tissue and Osteogenic Sarcomas of the Limbs - Sebastian Kapahnke; Matthias Bürger; Melanie Rusch; Grischa Hoffmann; Philipp Johannes Pauli; Lars Hummitzsch; Martin Albrecht; Roland Bertolini; Julia Bertolini; Rene Rusch; Rouven Berndt; Christoph Röcken; et al. (Cancer Reports, 2025)
ABSTRACT Background Soft tissue sarcomas (STS) and osteogenic sarcomas (OGS) of the limbs are rare diseases. Nowadays, most patients with STS or OGS undergo tumor resection and subsequent vascular reconstruction for potential limb preservation. Aims Due to very limited data on these complex surgical procedures, the aim of this single‐center, retrospective study was to evaluate the surgical and oncological outcomes of these patients. Methods From 2013 to 2023, demographic, clinical, surgical, and pathological data regarding tumor disease, surgical treatment, and postoperative care of a total of 10 patients with STS and OGS were identified and analyzed. Furthermore, overall survival (OS) and freedom from tumor recurrence (FFT) were retrospectively investigated among all patients. Results The mean age of the patients was 64.4 ± 22.24 years, and six women (60%) and four men (40%) were treated. Overall, 16 major arterial and venous vessels were resected and reconstructed: the lower extremity was affected in nine patients (90%). Autologous veins (n = 12, 75%), polytetrafluoroethylene (PTFE; n = 2, 12.5%), or cryopreserved allografts (n = 2, 12.5%) were mainly used for vascular reconstruction. The follow‐up ranged from 7 to 60 months, with a median OS of 48 months and a median FFT of 54 months. Overall, four patients (40%) developed local tumor recurrence at the primary surgical resection site or metastasis. The primary graft patency for all vascular reconstructions was 90% at the median follow‐up of 24 months. All revascularized limbs among these patients could be salvaged during the follow‐up period. Conclusion Treatment of patients with STS or OGS of the limbs and subsequent vascular reconstruction can be performed safely and effectively. The outcomes described in this cohort suggest that an interdisciplinary team, including vascular surgeons and a carefully planned and rigorous clinical approach, might positively influence the postoperative and oncological outcome and limb salvage.